Who Gets to Resist? - Mohammad Amaan Siddiqui (Politikon)
This paper examines contested definitions of terrorism and resistance, analyzing how the US and India instrumentalize such labels to suppress dissent and monopolize violence. Notably, it is worrisome that state narratives regarding who gets to resist remain dominant, despite national wars on terror being widely criticized. Moreover, it is puzzling that the US and India, states with historically diverging foreign policies, are today converging on security issues.  To address these dynamics, this paper employs case studies of the US and India to demonstrate how they use anti-terror laws and framing inconsistently, privileging elite interests over democratic processes. While the US focuses on opposing resistance against allies abroad, India directs aggression domestically, reflecting differences in federal structures and foreign policy ideologies. These findings provide theoretical insights regarding how states with divergent foreign policies can act similarly on matters of national security, offering timely insights into the US and India’s management of resistance, revealing systemic mechanisms that reinforce state authority under the guise of counterterrorism.